A study of inner-outer interactions in turbulent channel flows by interactive POD. Issue 1 (January 2021) - Wang, Hongping; Gao, Qi
Highlights: Interactive proper orthogonal decomposition is applied to investigate the interactions between the near-wall motions and the outer large-scale flow. The near-wall small scales are superposed and modulated by the outer large scales. The frequency modulation effect in the spanwise direction is the opposite of that in the streamwise direction. Abstract: The amplitude and frequency modulation of near-wall flow structures by the large-scale motions in outer regions is studied in turbulent channel flows. The proper orthogonal decomposition (POD) method is applied to investigate the interactions between the near-wall motions and the large-scale flow modes of the outer regions based on two datasets from direct numerical simulation of turbulent channel flows at Reynolds numbers of 550–1000. The fluctuations in the fields u +, v +, w + and Reynolds shear stress − ( u v ) + are studied to understand the mechanism of amplitude and frequency modulation of the near-wall structures by the outer large-scale motions. The amplitude modulation coefficient of the Reynolds shear stress is larger than that of the velocity components. The frequency modulation effect has an opposite influence in the spanwise direction compared to the streamwise direction. The streamwise characteristic frequency increases with increasing large-scale velocity. However, the spanwise characteristic frequency exhibits a decreasing trend with increasing large-scale velocity in the near-wall region.